2023
DOI: 10.21203/rs.3.rs-2902204/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of tDCS on mind wandering in adults with and without ADHD:

Abstract: Objective Individuals with attention deficit- hyperactivity disorder (ADHD) have a higher propensity to mind wandering. The ventromedial prefrontal cortex (vmPFC) and dorsolateral prefrontal cortex (dlPFC), which show reduced functionality in individuals with ADHD, are involved in mind wandering.Methods Forty adults with or without ADHD received transcranial direct current stimulation (tDCS) in three different conditions including anodal left dlPFC/cathodal right vmPFC stimulation, the reversed montage, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…In a separate study examining the impact of dorsolateral and ventromedial prefrontal cortex on emotion regulation in females with major depressive disorder (MDD), it was found that anodal left dlPFC/cathodal right vmPFC stimulation led to an improvement in working memory performance (Nejati, Majidinezhad, & Nitsche, 2022). Moreover, in both individuals with and without ADHD, the combination of anodal stimulation of the left dlPFC and cathodal stimulation of the right vmPFC resulted in enhanced performance on attention tasks and a reduction in mind wandering (Nejati, Majidinezhad, Yavari, & Nitsche, 2023). Previous studies have demonstrated that applying anodal stimulation to the left DLPFC can enhance neural excitability and improve cognitive function in individuals with diverse neuropsychiatric disorders, including ADHD (Sotnikova et al, 2017;Soff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study examining the impact of dorsolateral and ventromedial prefrontal cortex on emotion regulation in females with major depressive disorder (MDD), it was found that anodal left dlPFC/cathodal right vmPFC stimulation led to an improvement in working memory performance (Nejati, Majidinezhad, & Nitsche, 2022). Moreover, in both individuals with and without ADHD, the combination of anodal stimulation of the left dlPFC and cathodal stimulation of the right vmPFC resulted in enhanced performance on attention tasks and a reduction in mind wandering (Nejati, Majidinezhad, Yavari, & Nitsche, 2023). Previous studies have demonstrated that applying anodal stimulation to the left DLPFC can enhance neural excitability and improve cognitive function in individuals with diverse neuropsychiatric disorders, including ADHD (Sotnikova et al, 2017;Soff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%